Peran Orang Tua dan Guru dalam Meningkatkan Motivasi Hafalan Juz ‘Amma Siswa MI Ma’arif Ampih - Anjaly Qanitah; Benny Kurniawan; Bahrun Ali Murtopo (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
This study aims to determine the role of parents and teachers in increasing the motivationto memorize Juz 'Amma grade IV students of MI Ma'arif Ampih Bulus Pesantren Kebumen.This study uses a qualitative approach. The research instrument used was observation,interviews, and documentation. Data analysis techniques with data reduction, datapresentation, and draw conclusions. The results of the study are as follows (1) the role ofparents and teachers in increasing the motivation to memorize Juz 'Amma MI Ma'arif Ampih(a) the role of parents and teachers as facilitators (b) the role of parents and teachers ascompanions (c) the role of parents parents and teachers as motivators.